The SAGE handbook of geomorphology - Gregory, K. J. (Kenneth John); Goudie, Andrew (Thousand Oaks, California SAGE, 2011)
'The SAGE Handbook of Geomorphology' overviews a field of inquiry that is engaged in the organized and systematized descriptions of landforms and landscapes, and the processes responsible for forming, shaping and changing them.
Keywords: Geomorphology